2014
DOI: 10.2516/ogst/2014037
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Gas Injection Effect on the Asphaltene Phase Envelope

Abstract: and available online here Cet article fait partie du dossier thématique ci-dessous publié dans la revue OGST, Vol. 70, n°6, pp. 909-1132 et téléchargeable ici D o s s i e rOil & Gas Science and Technology -Rev. IFP Energies nouvelles, Vol. 70 (2015), No. 6, pp. 909-1132 Copyright © 2015, IFP Energies nouvelles > Editorial -Enhanced Oil Recovery (EOR), Asphaltenes and HydratesÉditorial -EOR «récupération assistée du pétrole», Asphaltènes et Hydrates D. Langevin and F. Baudin ENHANCED OIL RECOVERY (EOR) > HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
(33 reference statements)
2
11
0
1
Order By: Relevance
“…This event causes the solubility of asphaltene in the crude oil to increase until the lower onset point in which asphaltene dissolves again completely. The calculated solubility parameter of the oil supports this speculation (Bahrami et al, 2015). In fact, for each reservoir fluid, there is a minimum solubility point for asphaltene at fluid bubble point as mentioned by Tavakkoli (2013).…”
Section: Precipitation and Deposition Modeling Verificationsupporting
confidence: 77%
“…This event causes the solubility of asphaltene in the crude oil to increase until the lower onset point in which asphaltene dissolves again completely. The calculated solubility parameter of the oil supports this speculation (Bahrami et al, 2015). In fact, for each reservoir fluid, there is a minimum solubility point for asphaltene at fluid bubble point as mentioned by Tavakkoli (2013).…”
Section: Precipitation and Deposition Modeling Verificationsupporting
confidence: 77%
“…For instance, Gonzalez et al [143], [158] were the first to report that O-PC-SAFT predicts a crossover temperature, where an increment in CO2 injection does not promote asphaltene precipitation, but its solubility. Recently, Baharani et al [164], using a cubic EoS with an association term, conducted predictive calculations of AOPs for 10, 25, and 50% mol of CO2 injected into a reservoir fluid, and concluded that "the CO2 injection causes asphaltene precipitation to increase at high temperatures but below at certain crossover, the asphaltene stability increases. Then the CO2 can behave like an inhibitor or a precursor of asphaltene precipitation" [164].…”
Section: (A) (B)mentioning
confidence: 99%
“…Recently, Baharani et al [164], using a cubic EoS with an association term, conducted predictive calculations of AOPs for 10, 25, and 50% mol of CO2 injected into a reservoir fluid, and concluded that "the CO2 injection causes asphaltene precipitation to increase at high temperatures but below at certain crossover, the asphaltene stability increases. Then the CO2 can behave like an inhibitor or a precursor of asphaltene precipitation" [164]. Thus, both O-PC-SAFT and cubic EoS predict crossover temperatures.…”
Section: (A) (B)mentioning
confidence: 99%
“…for this reservoir oil based on the solubility parameter of asphaltene [48,49]. Overall, in terms of precipitated asphaltene and APE, CO 2 miscible injection could work as a good strategy in EOR purposes as long as the pressure is high.…”
Section: Eormentioning
confidence: 99%